Impact of Left Atrial Appendage Closure Combined with Catheter Ablation on Endocrine and Mechanical Cardiac Function in Patients with Atrial Fibrillation. (19th March 2022) - Yang, Jing; You, Ling; Liu, Mingqing; Zhang, Guangming; Feng, Liang; Liu, Yue; Geng, Xue; Wu, Jinglan; Xie, Ruiqin
Abstract : Background . The combined procedure of left atrial appendage closure (LAAC) and catheter ablation (CA) is a safe and feasible therapy to treat patients with atrial fibrillation (AF). However, the effect of the combined procedure on cardiac function remains unclear. This study aimed to investigate the changes in endocrine and mechanical function of the heart following the combined procedure. Methods . This retrospective study included 62 consecutive patients who underwent the combined procedure of AF ablation and WATCHMAN LAAC and 62 sex and age-matched patients who only received AF ablation. During follow-up, patients were examined for brain natriuretic peptide (BNP) levels to represent endocrine cardiac function. Mechanical cardiac function was assessed during echocardiographic examination by means of the LA ejection fraction, LA strain ( Ƹ ), and LA strain rate (SR). Results . (1) The BNP levels decreased acutely after the procedure, rose at day 3 postoperation, but trended downwards at 3 months postoperation in both groups. No significant difference was observed between the two groups. (2) LA ejection fraction, LA Ƹ, and SR exhibited a continuous upward trend over a 3-month follow-up in both groups. There was no significant difference in LA ejection fractions, SRe (the parameter of LA conduit function), and SRa (the parameter of LA booster pump function) between the two groups. However, the Ƹ and SRs (the parameters of LA reservoir function) improved in patients treated with CA alone. Conclusions . The combined procedure of LAAC and CA significantly improved the endocrine and mechanical function of the heart. Compared to simple CA, based on CA with LAAC intervention, it does not significantly change LA endocrine function but may lead to a decline in the LA reservoir function.